1998
DOI: 10.1046/j.1365-2893.1998.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin monotherapy in patients with chronic hepatitis C: a retrospective study of 95 patients

Abstract: Ribavirin is a purine nucleoside that inhibits the replication of a variety of RNA viruses and was shown to have a transient efficacy in chronic hepatitis C during short-term therapy. We have analysed retrospectively its efficacy in 95 patients with liver biopsy-proven chronic hepatitis C. Patients received oral ribavirin (600-1200 mg daily) for a mean duration of 11 months. Alanine aminotransferase (ALT) levels returned to normal values in 38 patients (40%) and decreased by more than 50% in 20 other patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 23 publications
3
42
1
Order By: Relevance
“…However, ribavirin incorporation should occur at best only once/7000 nucleotides incorporated; that is, approximately once per genome. As a result, several cycles of replication may be necessary to cause a significant drop in production of infectious virus, consistent with the reduced efficacy of ribavirin monotherapy for treatment of HCV infection (15). We also observed a substantial block to elongation of nascent RNA when ribavirin was present in the template (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, ribavirin incorporation should occur at best only once/7000 nucleotides incorporated; that is, approximately once per genome. As a result, several cycles of replication may be necessary to cause a significant drop in production of infectious virus, consistent with the reduced efficacy of ribavirin monotherapy for treatment of HCV infection (15). We also observed a substantial block to elongation of nascent RNA when ribavirin was present in the template (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…In this case, a single incorporation per genome may be more than sufficient to cause a substantial antiviral effect. If this is the case, then the reduced efficacy of ribavirin monotherapy may be a reflection of the use of reverse transcriptase-polymerase chain reaction as an indicator of viral load instead of a direct analysis of virus infectivity (15). HCV RNA may be stable for substantial periods of time in cells and defective RNA may be packaged if the appropriate signals remain intact.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cameron and colleagues (21,22) showed that ribavirin can be misincorporated into mRNA by viral RNA-dependent RNA polymerases because of its chemical similarity to guanosine, and this outcome leads to lethal mutagenesis of genomes of polio and HCV. Ribavirin triphosphate (RTP) binds the HCV polymerase with an observed dissociation constant (K d ) of 0.58 mM (23), which is consistent with micromolar concentrations necessary to achieve a therapeutic effect against HCV clinically (24). In addition to effects at millimolar concentrations, ribavirin is also active at micromolar concentrations.…”
mentioning
confidence: 72%
“…A biochemical response was established. In 10% of the patients there was HCV RNA clearance (34). The data show only one study for the combination therapy with Inosine pranobex and Ribavirin (more than 20 years ago) in patients with HIV infection.…”
Section: Medinform 37mentioning
confidence: 93%